PNEUMOCOCCAL INFECTIONS AND VACCINATION - CAN PREVENTION REDUCE THE BURDEN OF THE ILLNESS - L.S. Namazova; M.G. Galitskaya; M.V. Fedoseenko (Union of pediatricians of Russia, 2007)
The article gives the findings of the widest ranging research carried on in the USA to appraise the efficiency of vaccination by the study of the hospitalization frequency for pneumonia of any etiology and for dehydration after the program of immunization by the conjugated pneumococcal vaccine (for the children under 2 years old) was launched by the government. The authors made use of the experimental approach. They revealed a significant reduction of the hospitalization frequency for pneumonia (by 39%) along with the invariable indices of the studied parameter in the event of dehydration. they convincingly showed how exactly it is possible to reduce the spread of pneumococcal pneumonia among children by the vaccination. they acquired the data, which proved the findings of other studies pertaining to the positive effects of the children's vaccination by the conjugated pneumococcal vaccine.Key words: pneumonia, pneumococcal pneumonia, hospitalization, vaccination, efficiency, children.